Expandable Fasteners for Orthopaedic Applications: Design and Development of the EXF Screw - Oldakowski, Matthew Peter (Curtin University, 2017)
Orthopaedic screw fixation failure is a significant problem which causes severe health complications and costly revision surgeries. This project investigated the potential to improve surgical outcomes with expandable fasteners and the effect of the design parameters and bone quality on the performance of expandable fasteners. A novel expandable screw was developed, the design was optimised and proof-of-concept testing was performed to demonstrate increased fixation strength whilst ensuring long-term removability and acceptable safety margin.